PENGARUH PEMBERIAN ROSE EFFLEURAGE TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF PADA PERSALINAN NORMAL PRIMIGRAVIDA DI BIDAN PRAKTIK MANDIRI ERNITA KOTA PEKANBARU - Jasmi Jasmi; Elly Susilawati; Ana Andriana (JOMIS (Journal of Midwifery Science), 2020)
Birth pain can cause maternal discomfort such as fatigue, frustration, despair, and stress. The preliminary survey at PMB Ernita of Pekanbaru showed that there were 60% of the mothers that suffered moderate pain and 40% of them experienced severe pain. The intensity of labor pain can be reduced by giving a rose effleurage that can produce endorphin so that it stimulates a sense of relaxation. This pre-experimental research used a one group pre-test study post-test design carried out in March to June 2018. The population was primigravidae mothers in the first stage of labor taken using purposive sampling technique. The results showed that the average intensity of pain in parturient women before and after administration of rose effleurage was 6.00 and 4.60, respectively. The result of statistic test with Wilcoxon test on 95% confidence degree showed that there was the effect of rose effleurage stage on pain intensity in the active stage of labor (p value = 0.000). It is then suggested that rose effleurage can be applied as an alternative method which aims to reduce the intensity of labor pain at the time of active phase.